Analisis Penetapan Harga Sewa Pada Unit Rumah Susun (Studi Kasus: Rusun Tingkat Tinggi Pasar Rumput, Jakarta Selatan) - Yanuar Riska, Sofi; Junita K, Dewi; Arifin, Samsyul (Indonesian Society of Applied Science, 2023)
Flats are often referred to as simple versions of apartments. Rusun Tingkat Tinggi Pasar Rumput is a flat that was built to meet the housing needs of lower-middle-income and low-income people whose construction gets facilities and government assistance. In this study, to determine the rental price of the flats, what is needed is to know the total cost of development. The data collection that is done to get the rental price is to calculate the volume of work and make a budget plan and calculate other development costs. The result of the analysis is that the total cost for the construction of the Grass Market High-Level Flats is Rp. 668,648,547,822.72,-. The price of the apartment rental unit by the available cost analysis is Rp. 877,657,389. To determine the price increase each year, depending on the capitalization rate each year. The increase in rental prices for flats for 2020, 2021, and 2022 for a capitalization level of 7%, namely Rp. 1,000,529.42, Rp. 1,061,965.44, and Rp. 1,123,401.46. A capitalization level of 12%, which is Rp. 1,088,295 ,16 , Rp 1,193,614,05, and Rp 1,298,982,94.